Fifth International Conference on Advances in Civil, Structural and Mechanical Engineering - CSM 2017 2017
DOI: 10.15224/978-1-63248-132-0-56
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on composite polymer and silica fume rubber aggregate pervious concrete

Abstract: Abstract-Many researchers are trying to obtain a pervious concrete with better physical and mechanical properties to be used in pavement. To achieve the optimized pervious concrete, different researchers have been using different materials, especially those waste materials which are existing worldwide, specifically in the compactly populated areas. Discarded tires are among them and rubber tire particles are being currently used to be considered as recycled waste materials. In this paper a combination of polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Embora muitos desses estudos relatem um bom desempenho técnico do concreto permeável, no que se diz respeito à resistência à compressão, flexão e permeabilidade, suas propriedades físico-mecânicas variam consideravelmente em função do tipo de resíduo aplicado (TOGHROLI et al, 2017). O RBRO é um resíduo produzido em larga escala no Brasil e pouco se conhece acerca de concretos permeáveis produzidos com esse material.…”
Section: Figura 1 -Comparação Entre Paver Comum E Paver Permeávelunclassified
“…Embora muitos desses estudos relatem um bom desempenho técnico do concreto permeável, no que se diz respeito à resistência à compressão, flexão e permeabilidade, suas propriedades físico-mecânicas variam consideravelmente em função do tipo de resíduo aplicado (TOGHROLI et al, 2017). O RBRO é um resíduo produzido em larga escala no Brasil e pouco se conhece acerca de concretos permeáveis produzidos com esse material.…”
Section: Figura 1 -Comparação Entre Paver Comum E Paver Permeávelunclassified
“…Shariati et al [22] showed that concrete permeability could be improved by making waste tires into aggregates. Toghroli et al [23] found that the coupling of composite polymer, silica fume, and rubber aggregate could improve the mechanical properties and water permeability of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…As water is used and removed from the small holes in the hydrated cement network in HPC mixes, large inward Laplace pressures occur [ 34 ]. These pressures are significant enough to generate autogenous shrinkage, a bulk volumetric collapsing of the system that can result in early age cracks and failure of the structure, particularly if the concrete is restricted against reinforcements, forms, or even other concrete [ 17 , 39 , 78 , 79 , 80 , 81 , 82 , 83 ]. Extra water can be given externally during the curing stage to prevent self-desiccation and counterbalance part of this early age shrinkage through the use of wet blankets, hoses, or sprinklers.…”
Section: Introductionmentioning
confidence: 99%